DESAIN TURBIN TESLA SEBAGAI PEMBANGKIT LISTRIK TENAGA AIR - Marfizal, Marfizal; Wardianto, Dedi; Sufiyanto, Sufiyanto; Yusuf, Muhammad (Jurnal Teknologi dan Vokasi, 2025)
This research focuses on the design of the Tesla Turbine as a simple Hydroelectric Power Plant. This design focuses on the main dimensions of the Tesla Turbine such as diameter, distance, disk thickness and other supporting components. This Tesla turbine is designed for. Head 9.8 m and discharge 0.028 m3/s so that the disk dimensions are obtained: distance between disks (b)= 0.8 mm, disk diameter (D)=160 mm, disk thickness (t)=0.40 mm, aspect ratio (ϵ)=0 mm, Ri= 24 mm, number of disks (N)=13 disks. For Nozzle dimensions: Nozzle surface area (An)=0.002m2, Nozzle diameter (Dn)=0.051m, Nozzle width =16.4mm. For the turbine housing, the following dimensions are obtained: turbine housing width ()=200mm, turbine housing height ()=200mm, wall thickness ()=8mm, turbine housing diameter ()=166mm, turbine housing thickness =40.26mm